Mendidik Anak melalui Bermain - Pahrul, Yolanda; Herawati, Susi; Mahfudoh, Siti; Nusmiyati, Nusmiyati; Ulfah, Maria; Sa’adiyah, Halimah; Fauziah, Chusnul; Maemaunah, Maemaunah; Handayani, Tri; Mardiyanti, Yanti; Kurniawati, Ade; Nurhayati, Nurhayati; Hasanah, Siti; Suhaeti, Eti; Samhudi, Moh. (Universitas Pahlawan Tuanku Tambusai, 2025)
As educators, they contribute greatly to starting to develop children's abilities through play by choosing and implementing the right strategies and media as learning methods or models that are in accordance with the development of students. One of the learning methods that can be chosen by teachers to improve the ability to educate children through play. This community service is carried out through workshop activities with PAUD teachers and parents. The teachers and parents are very enthusiastic about the implementation of this PKM. They asked a lot about how early childhood education through play. They admitted that there was a lot of homework and improvements made for children's education through play.